Gaya Komunikasi Kepemimpinan Perempuan dalam Perusahaan Media - Oktavia Permatasari; Alfiana, Ulfa (Universitas Djuanda Bogor, 2026)
This study examines the communication styles of female leaders in a local print media company, the Metropolitan Daily, in Bogor, which is transforming along with current digital developments. Leadership is a fundamental element in organizations, and effective communication is key to success, especially for female leaders. This study examines the leadership communication style of the Metropolitan Daily Production Manager, Febriula Sindisari. This study uses a descriptive qualitative method with a case study approach. The purpose of the study is to identify the communication styles of female leaders in the media company and the interpersonal interactions between female leaders and employees. The main theories used are leadership communication theory and gender communication theory. The results show that Sindisari's communication style tends to be equalitarian, flexible, situational, and familial, prioritizing discussion and deliberation in decision-making. The communication flow is vertical (top-down and bottom-up) and horizontal, often utilizing informal channels to absorb staff aspirations. Sindisari's leadership style is transformational and participatory, encouraging collaboration, empathy, and objectivity in problem-solving. Subordinate perceptions indicate clear communication and openness to input. Female leaders in the media industry have the potential to be agents of change in facing the challenges of the digital era.